Clinical and computational exploration of red date fruit vinegar: synergistic effects on cardiovascular and type 2 diabetes pathways - Ali, Zeshan; Rafique, Hamad; Tahir, Rana Adnan; Saeed, Tania; Rasheed, Muhamad Amir; Khan, Ishrat; Alsulami, Tawfiq; Shahzadi, Muqadas; Amir, Mariam Laraib; Althawab, Suleiman A.; Cui, Fangchao (Frontiers in Nutrition, 2025)
IntroductionDates (Phoenix dactylifera), often questioned for their high sugar content, may provide anti-diabetic benefits through their phytochemicals. Date vinegar offers a potentially effective alternative with reduced sugar content and enhanced bioactivity. This study evaluated the effects of date vinegar on glycemic control and lipid profiles in adults with type 2 diabetes mellitus (T2DM) and dyslipidemia while exploring the molecular mechanisms of its bioactive compounds in managing cardiovascular diseases (CVDs) and T2DM.MethodsA 10-week randomized controlled trial assessed the clinical effects of date vinegar. Complementary experiments explored therapeutic mechanisms through computational analysis and assessed sugar reduction and bioactive preservation under varying drying conditions. Fifty adults with T2DM and dyslipidemia were randomized into two groups: 25 participants received 20 mL of date vinegar daily, while 25 received a placebo. Clinical parameters were measured, including HbA1c, LDL cholesterol, and fasting blood sugar. Computational docking and molecular dynamics simulations investigated interactions of bioactive compounds with key protein targets.ResultsSignificant improvements were observed: HbA1c reduced from 6.85 to 6.08%, LDL cholesterol from 121.05 to 111.09 mg/dL, and fasting blood sugar from 168.4 to 147.6 mg/dL (p < 0.05). Key compounds with stable protein-ligand complexes confirmed were bound to targets such as ACE, β1AR, hATRs, AR, DPP-IV, and SGLT1. Higher drying temperatures reduced sugar content to match fresh dates but compromised bioactive integrity.ConclusionDate vinegar offers a dual target therapeutic strategy for managing T2DM and CVDs, supported by clinical and computational findings.